Development of Augmented Reality Learning Media in Chemistry Subject High School - Priyanto, Priyanto; Sumarwan, Sumarwan (Universitas Dharma Wacana, 2023)
This study aims to develop chemical bond Augmented Reality (AR) learning media based on Android applications and determine their feasibility. AR media is used in Chemistry class X SMA. Topics developed in this medium are covalent bonding materials and molecular shapes. This Research and Development research was conducted using the multimedia development life cycle (MDLC) model with the stages of concept, design, material collecting, assembly, testing, and distribution. At the testing stage, a feasibility test is carried out through two stages of the validation test, namely the alpha test and beta test. The results of this study indicate that: (1) AR learning media products in chemistry class X were successfully developed with covalent bonds and molecular shapes; (2) the results of testing AR learning media in chemistry Class X obtained very decent results with a percentage of 89.58% in media testing, 91.25% in material testing, and 80.20% in testing prospective users; and (3) this AR learning media received a positive response both from students as potential users and from the subject teacher concerned regarding the easy-to-understand material due to clear visualization and examples as well as an attractive appearance.